Consumer perspectives towards buying green products: A survey of food sector in Tanga Municipality - Uhagile, Glory T (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of the degree of Masters of Business Administration in Corporate Management (MBA-CM) of Mzumbe University